Prognostic Role of Blood Markers in Primary Central Nervous System Lymphoma Patients Treated With High-Dose Methotrexate-Based Therapy - Luo, Qian; Yang, Chunli; Fu, Chunxi; Wu, Wanchun; Wei, Yi; Zou, Liqun (Frontiers in Oncology, 2021)
Purpose: Primary central nervous system lymphoma (PCNSL) is a rare type of extra-nodal non-Hodgkin lymphoma, but the prognostic value of blood parameters indicating systemic inflammation and nutritional status remains unknown. We aim to explore the prognostic role of blood parameters in PCNSL. Methods: All PCNSL patients diagnosed at West China Hospital between February 2011 and February 2020 were retrospectively screened. For patients who were initially treated with high-dose methotrexate (HD-MTX)-based therapy, clinical data were collected. Survival analyses were performed using the Kaplan–Meier method and multivariable Cox proportional regression. The accuracies of different multivariate models were assessed by Harrell's C statistical analysis (C-index). Results: Sixty patients were included. Median overall survival (OS) was 4.8 ± 3.7 years, and median progression-free survival (PFS) was 1.9 ± 1.3 years. In the multivariate analysis, hemoglobin (Hb) (HR 3.940, p = 0.013), neutrophil–lymphocyte ratio (NLR) (HR 10.548, p = 0.034), and total bilirubin (TBIL) (HR 3.429, p = 0.004) had independent prognostic values for PFS, while lymphocyte–monocyte ratio (LMR) (HR 6.195, p = 0.039), systemic immune-inflammation index (SII) (HR 5.144, p = 0.012), and TBIL (HR 3.892, p = 0.009) were independently related to OS. The C-index of the Memorial Sloan-Kettering Cancer Center (MSKCC) score increased from 0.57 to 0.72 when SII and TBIL were combined. Conclusions: Our study indicated that pretreatment Hb, NLR, SII, LMR, and TBIL were convenient prognostic factors in PCNSL. Adding SII and TBIL to the MSKCC score can better predict the survival of PCNSL based on HD-MTX regimens.